Product Diversification Strategy in Agribusiness to Increase Farmers' Profits and Economic Stability - Rahmasari, Liisa Firhani; Abidin , Zainal (International Journal of Economics (IJEC), 2025)
Product diversification in agribusiness is an important strategy in increasing farmers' profits and economic stability, especially amidst the challenges of commodity price fluctuations, climate change, and dependence on one type of product. This study aims to analyze the effectiveness of product diversification in agribusiness and identify the most appropriate strategy for farmers to increase their profitability and economic resilience. Using a descriptive qualitative approach, this study was conducted in Berastagi , North Sumatra, as one of the areas with a rapidly growing agribusiness sector. Data were collected through observation, interviews, surveys, and literature studies, then analyzed using a thematic approach to understand diversification patterns and their impacts on farmers' economy. The results of the study indicate that the diversification strategies implemented in Berastagi include horizontal diversification (planting various types of commodities), vertical diversification (processing agricultural products into value-added products), and lateral diversification (development of agrotourism and livestock businesses). Diversification has been shown to increase farmers' income, reduce business risks due to price fluctuations, and expand market access. The success of this strategy is influenced by several main factors, namely access to markets, availability of capital, application of technology, and support from the government and related institutions. However, challenges such as limited capital, lack of skills in product processing, market uncertainty, and complex regulations are still obstacles in implementing diversification. Therefore, a more targeted strategy is needed, such as strengthening sustainable agricultural systems, technological innovation in processing and marketing, and collaboration between farmers, the government, and the private sector. The results of this study are expected to provide insight for farmers, policy makers, and agribusiness actors in developing more effective and sustainable diversification strategies, so as to improve farmer welfare and the resilience of the agribusiness sector as a whole.